Understanding Sulfur Redox Mechanisms in Different Electrolytes for Room-Temperature Na–S Batteries - Liu, Hanwen (Nanomicro Lett, 2021)
This work reports influence of two different electrolytes, carbonate ester and ether electrolytes, on the sulfur redox reactions in room-temperature Na–S batteries. Two sulfur cathodes with different S loading ratio and status are investigated. A sulfur-rich composite with most sulfur dispersed on the surface of a carbon host can realize a high loading ratio (72% S). In contrast, a confined sulfur sample can encapsulate S into the pores of the carbon host with a low loading ratio (44% S). In carbonate ester electrolyte, only the sulfur trapped in porous structures is active via ‘solid–solid’ behavior during cycling. The S cathode with high surface sulfur shows poor reversible capacity because of the severe side reactions between the surface polysulfides and the carbonate ester solvents. To improve the capacity of the sulfur-rich cathode, ether electrolyte with NaNO(3) additive is explored to realize a ‘solid–liquid’ sulfur redox process and confine the shuttle effect of the dissolved polysulfides. As a result, the sulfur-rich cathode achieved high reversible capacity (483 mAh g(−1)), corresponding to a specific energy of 362 Wh kg(−1) after 200 cycles, shedding light on the use of ether electrolyte for high-loading sulfur cathode. [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s40820-021-00648-w.